2017
DOI: 10.1038/s41598-017-00397-0
|View full text |Cite
|
Sign up to set email alerts
|

Remote control of glucose homeostasis in vivo using photopharmacology

Abstract: Photopharmacology describes the use of light to precisely deliver drug activity in space and time. Such approaches promise to improve drug specificity by reducing off-target effects. As a proof-of-concept, we have subjected the fourth generation photoswitchable sulfonylurea JB253 to comprehensive toxicology assessment, including mutagenicity and maximum/repeated tolerated dose studies, as well as in vivo testing in rodents. Here, we show that JB253 is well-tolerated with minimal mutagenicity and can be used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…2016 b ). However, there are disadvantages with photopharmacology: the lack of binary switch can complicate the optical control of cell function, UV illumination is generally required for the isomerisation step and toxicity and metabolite production need to be carefully assessed, just as for any drug, although the azobenzene itself appears to be well tolerated ( Mehta et al . 2017 ).…”
Section: New Tools For Understanding Beta Cell Heterogeneitymentioning
confidence: 99%
“…2016 b ). However, there are disadvantages with photopharmacology: the lack of binary switch can complicate the optical control of cell function, UV illumination is generally required for the isomerisation step and toxicity and metabolite production need to be carefully assessed, just as for any drug, although the azobenzene itself appears to be well tolerated ( Mehta et al . 2017 ).…”
Section: New Tools For Understanding Beta Cell Heterogeneitymentioning
confidence: 99%
“…It should be noted that the stability of azobenzene compounds introduced ex vivo or in vivo has to be evaluated on a case-to-case basis as degradation of the diazene unit might occur depending on cell environment or azoreductase expression. While we have shown that this is not the case for polar compounds such as JB253 68 and JB558 69 , careful evaluation has to be performed before any clinical applications can be envisioned.…”
Section: Discussionmentioning
confidence: 98%
“…Remarkably and surprisingly, GPCRs, next to enzymes the most important drug targets, have only been addressed very recently with photoswitchable tool compounds. Targets have been the metabotropic glutamate receptors, the class B glucagon‐like peptide‐1 receptor, the adenosine, the dopamine and Ό‐opioid receptor, and the muscarinic acetylcholine receptor . At the same time of the preparation of this manuscript, Westphal et al.…”
Section: Introductionmentioning
confidence: 99%